Structured risk assessment for reduction of multiple risk outcomes in a secure mental health setting:use of the START - Dickens, Geoffrey L. (2018)
Background: Structured risk assessment is commonly used in secure settings to aid prediction and prevention of risky behaviours; the expected benefits have rarely been investigated. Aims: The aim of the study is to determine whether adverse outcomes (physical and verbal aggression, self-harm, victimisation, self-neglect, unauthorised leave and substance abuse) reduced after patients were assessed with the Short-term Assessment of Risk and Treatability (START). Methods: In a naturalistic study, anonymised demographic and clinical information was collected from 50 male patients. Data included START assessment and frequency of target behaviour for 3 months before and after first assessment. Chi-square and linear mixed models analyses were used to determine whether there was any change in the behaviours of interest. Results: There were no significant changes in physical or verbal aggression over time, although a tendency towards fewer incidents was apparent. Other adverse behaviours were very infrequent at baseline, precluding adequate analysis. Conclusions: In this small sample, START did not achieve its primary purpose of significant reduction in adverse behaviours. Although our sample size was informed by a power calculation, we may have over-estimated the size of anticipated change. Further, the 3-month comparison periods before and after the assessment follow-up period were rather short. Accordingly, we recommend more research on the value of this tool in practice rather than discontinuing its use